Psychological Characteristics of Preschool Children - Jumaevna , Nasiba Yarashova (Research Parks Publishing LLC, 2022)
The role of pre-school educational institutions in the formation of a child's personality and development of his interests in the field of knowledge, ensuring its physical and mental development, as well as the proper organization of the preparation of children for school education can not be overestimated.